Michelangelo. - Stearns, Monroe (New York, F. Watts, 1970)
The life of the Renaissance sculptor, painter, architect, and poet.
Bibliography: p. [237]-239.
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.